The EFFECT OF EDUCATION THROUGH VIDEO TOWARDS SELF CARE MANAGEMENT ON GLAUCOMA PATIENTS IN THE EYE CLINIC OF RSD MANGUSADA, BADUNG REGENCY - Luh suandewi (NHM PRESS, 2021)
Glaucoma is a disease that the patient experiences for life. Patients need self-care management to undergo a lifelong treatment process and prevent blindness. Self-care management in glaucoma patients can encourage patients to take prevention and treatment that requires collaboration with health workers so that they can manage their health independently. This study purposed to determine the effect of video education towards self-care management on glaucoma patients in the Eye Clinic of RSD Mangusada, Badung Regency. The method used in this study is a pre-experimental research design with pre-test and post-test one-group design. The samples were 44 respondents with a consecutive sampling technique. Data were collected by using a self-care management questionnaire on glaucoma patients. Data were analyzed using the Wilcoxon test. The results of the study before education through video was implemented, most of the self-care management were moderate as many as 22 people (50%), there was an increase after being implemented education through video, most of the good self-care management were 30 people (68.2%). Analysis of the effect of education via video on self-care management in glaucoma patients obtained p-value <0.001. There is an effect of education via video towards self-care management on glaucoma patients in the Eye Clinic of RSD Mangusada, Badung Regency. The recommendations of this study are expected to be input for nurses to always provide education about self-care for glaucoma patients to prevent blindness.